Comparison Between Evendo Score and Baveno VII Criteria for Predicting Esophageal Varices in Cirrhosis Patients - Bestari, Muhamad Begawan; Alisjahbana, Bachti; Baskoro, Toni (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: The EVendo score and Baveno VII criteria are non-invasive methods in predicting the presence of esophageal varices in patients with cirrhosis. The EVendo score is more practical to use in daily practice than the Baveno VII criteria because it does not require a liver stiffness measurement. This study aims to compare the performance of the EVendo score with the Baveno VII criteria for predicting the presence of esophageal varices in patients with liver cirrhosis.Methods: This study was diagnostic study with cross-sectional approach on cirrhosis patients who had previously undergone upper gastrointestinal endoscopy who had laboratory examination data and liver stiffness measurement values. Based on the existing data, calculation and comparison of the diagnostic value of the EVendo score and the Baveno VII criteria were carried out. The research was conducted at dr. Hasan Sadikin based on patient data from April 2017 to May 2023.    Results: The Evendo score had a sensitivity of 80.5%, specificity 50%, PPV 84.6%, NPV 42.9%, positive likelihood ratio 1.61, and negative likelihood ratio 0.39. The Baveno VII criteria had a sensitivity of 95.1%, specificity of 25%, PPV 81.2%, NPV 42.9%, positive likelihood ratio 1.27, and negative likelihood ratio 0.2.Conclusion: The results of this study show that the EVendo score and Baveno VII criteria have high sensitiviy but low specificity for predicting esophageal varices in patients with liver cirrhosis.